Effects of School Nurse-Led Asthma Interventions for Students: A Systematic Review. - Yoon, Jaehee; Seo, Hyun-Ju; Cho, Jeonghyun; Lee, Su Jung; Lee, Ji Sung; Choi, Yumi; Noh, Suyeon (Journal of School Nursing, 2026)
School nurse-led asthma interventions play a critical role in managing asthma among students. This study evaluates the effectiveness and key components of interventions for children with asthma. A systematic search of multiple databases was conducted up to September 2023. Two independent reviewers assessed the risk of bias using the Mixed Methods Appraisal Tool, and descriptive evidence synthesis with albatross plots was used to analyze the findings. Results revealed that school nurse-led asthma interventions positively influenced asthma symptoms, medication use, asthma-related quality of life, and self-management in schoolchildren. However, emergency visits, hospitalization, and absence outcomes remain inconclusive. Effective components identified across studies included chronic disease management, direct care, and collaborative communication. Further, well-designed randomized controlled trials with standardized outcome measurements are needed to examine objective outcomes, including emergency visits, hospitalization, and school absences, and strengthen the evidence base for school nurse-led asthma interventions.